Egyptian Propolis Alleviates Gentamicin-Induced Nephrotoxicity in Rats - Atta, Attia H.; Nasr, Soad M.; Mouneir, Samar M.; Abdel-Aziem4, Sekena H.; Nassar, Somia A. (JOURNAL OF ADVANCES IN CHEMISTRY, 2010)
The objective of this study was to evaluate the effectiveness of oral administration of ethanol extract of propolis against gentamicin induced nephrotoxicity in rats. Oral administration of ethanol extract of propolis (EEP) at doses 25, 50 and 100 mg/kg.b.wt. orally/daily for 7 days) against gentamicin- (GM) at dose 100 mg/kg b.wt., i.p./daily for 7days) induced nephrotoxicity in six equal groups of adult male Sprague-Dawley rats. Blood was collected 24 h after the last injection for determination of serum creatinine, urea, and aspartate aminotransferase (AST) activity. Rats were euthanized and kidney tissue specimens were collected for determination of oxidative/antioxidative biomarkers, gene expression for antioxidative enzymes and DNA fragmentation. Significant increase in serum creatinine, urea and AST activity at the same time, and a depletion of aspartate aminotransferase activity was recorded in renal homogenate of GM only–treated rats compared to control group. Lipid peroxidation in renal tissue showed significant elevation in GM-only treated group, however, superoxide dismutase, glutathione peroxidase and catalase and its gene expression were markedly decreased. DNA fragmentation was significantly increased in renal tissue of GM- only treated rats. Oral administration of EEP exhibited curative effects by reversing GM-induced alterations in serum biochemical and renal tissue oxidative stress biomarkers. In conclusion, propolis is effective in preventing or ameliorating oxidative stress of gentamicin.